(untitled) (Bangladesh Journal of Medical Science, 2019)
Objective: Female sex workers (FSWs) under 20 years of age range from 1,000 to 575,000 in different cities and countries across the globe. There is only a handful of information on the reproductive health (RH) issues of these younger FSWs in the perspective of service utilization and healthcare system. We reviewed existing literature with a view to describe the reproductive health problems, service utilization, and service availability as well as information sources among the FSWs ages <20 years. Materials and methods: A web-based search using Google, Google Scholar, MEDLINE/ PubMed/ PubMed Central, HINARI and JSTOR was performed in English Language. The prevalence of a health issue and percentage of service utilization had been shown using ranges of minimum and maximum value which were calculated by different studies. Results: Findings identified the following RH problems: unintended pregnancies (52% - 95%), induced abortion (51% - 53%), repeated or multiple abortions (13% - 43%), childbirth experiences, sexually transmitted infections (74%-84%), HIV (1% - 60.6%), violence (beaten, robbed, not paid, forced or coerced sex, rape) and mental disorders (depression, suicidal thoughts). The consistent use of condom (26%-55%) was not satisfactory. Overall 64% of under 20 years FSWs reported little or no access to healthcare in the previous year and access to RH information sources was also poor. Conclusion: This review has potentially meant to bring forward the RH issues of younger FSWs to the policy makers and programme planners to implement targeted reproductive health interventions for the FSWs ages <20 years. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.17-31